Facile preparation of ultraviolet resistant "hard armors" on poly(p-phenylene benzobisoxazole) fibers through heat-induced surface treatment. (May 2022) - Hao, Mengyuan; Hu, Zhen; Zhang, Yonggang; Qian, Xin; Liu, Li; Yang, Jiaming; Wang, Xuefei; Zhi, Jianhai; Huang, Yudong; Shi, Xiaolu
Highlights: The coaxial poly(p-phenylene benzobisoxazole) fibers with ultraviolet resistant "hard armors" were prepared through heat treatment. The transformation of UV sensitive oxazole groups into non-conjugated six membered ring structures could be achieved in the fiber surface. Fiber's UV-resistance effect has significantly improved with over 90% strength retention after 800 h UV aging. The 33.5% increase of Young's modulus, 74% increase of compressive strength and 64% interfacial shearing strength (IFSS) improvement were achieved. Abstract: In terms of high-performance organic fibers such as poly(p-phenylene benzobisoxazole) (PBO) fiber, the anti-ultraviolet (UV) property is crucial for their applications in extreme conditions. In this work, excellent UV resistance was obtained through creating a thermal oxidized PBO sheath on PBO fiber. In detail, the peripheral UV sensitive oxazole groups were transformed into non-conjusix-memberedmbered rings after heat-induced gradient thermal oxidation, which could reduce the UV sensitivity of PBO fiber and release energy produced by UV radiation through molecular vibration. The efficiency had been verified through UV-aging tests, and the results indicated that more than 90% of the fiber's tensile strength was retained and the surface defects after 800 h UV aging was also effectively decreased. There were also considerable improvements in the mechanical properties of PBO fiber. For instance, Young's modulus and compressive strength of PBO fiber increased by 33.5% and 74%, respectively, along with the absence of yield zone. Meanwhile, the interfacial shearing strength (IFSS) of PBO reinforced epoxy resin composites increased by 64% with the introduction of non-conjugated structure. The inhomogeneous reduction in rigid-rod backbones resulted in the maintenance of internal microfibrils and decrease in peripheral microfibrils, and accordingly relieved the compressive damage. Enhancement of its interfacial property possibly resulted from increased surface roughness and decreased inert rigid-rod structure.